Optimalisasi Belanja Daerah Pada Badan Pengelolaan Keuangan Kabupaten Aceh Barat Daya - Fitri, Rima Hidayatul; Fatmayanti, Fatmayanti (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
Expenditures in the budget realization report have great significance because they reflect the use of public funds obtained from regional taxes. The interest of the community as the party who contributes these funds through taxes, lies in the desire to assess the extent to which the use of these funds is in accordance with the objectives, effective, efficient and focused on the public interest. Spending analysis can be done using the spending variance ratio, spending growth ratio, spending harmony ratio and spending efficiency ratio. The aim of this research is to analyze regional spending performance through the variance ratio, growth, harmony and efficiency of regional spending at the Southwest Aceh Regency Financial Management Agency. This research is quantitative descriptive. Data was collected through documentation techniques. This research uses secondary data in the form of the Budget Realization Report of the Southwest Aceh Regency Financial Management Agency. The results of this research can be concluded that the calculation results of the spending variance ratio show good results with an average of -14.12%. The calculation results of the expenditure growth ratio show positive results with an average of 7.84%. The calculation results of the expenditure harmony ratio show that the operating expenditure results are an average of 63.12%, while for capital expenditure it is 24.14%. The calculation results of the shopping efficiency ratio show an average result of 86.39%, which means that if you look at the shopping efficiency criteria, it is included in the quite efficient category.